DESIGN OF THE SUBJECT O F WEATHER REPORT AS A COURSE UNIT IN LANGUAGE TEACHING - Coşkun, Hasan (Journal of Education Culture and Society, 2020)
Aim. In Turkey, in connection with the Bologna process, German is a foreign language course. In this study, the subject of a weather report (forecast) was planned for the German courses. The purpose of this study is the preparation, implementation and evaluation of a sample lesson to describe the selection of the subject of a weather report for the German courses taught at schools and universities. Methods. This study was conducted by qualitative research (Yıldırım & Şimşek, 2008, pp. 187-193). During the 2019 / 2020 academic year, I taught the subject of a weather report students in German courses and 38 students in master courses. Result and Conclusion. It was observed that participants talk about the weather in their hometown and in the places where they go on vacation. In addition to the subject discussed in class, the method implemented in the lesson and the planning of the course according to the method, play an important role in the continuation of this interest. Origin. The students who were in German speaking countries under the Erasmus program participate in German courses to maintain their fluency in German language. In order to conduct German courses effectively for different purposes, and for participants coming from different countries and students with different levels of fluency, a suitable method should be developed.